Safety, Pharmacodynamic Response, and Treatment Satisfaction With OnabotulinumtoxinA 40 U, 60 U, and 80 U in Subjects With Moderate to Severe Dynamic Glabellar Lines. (15th June 2022) - Joseph, John H; Maas, Corey; Palm, Melanie D; Lain, Edward; Glaser, Dee Anna; Bruce, Suzanne; Yoelin, Steven; Cox, Sue Ellen; Fagien, Steven; Sangha, Sara; Maltman, John; Lei, Xiaofang; et al.
Abstract: Background: OnabotulinumtoxinA 20 U reduces glabellar line (GL) severity at maximum frown for approximately 3 to 4 months. Small studies have suggested that >20-U doses may increase the efficacy and duration of response for GLs. Objectives: The aim of this study was to evaluate safety, pharmacodynamic response, and treatment satisfaction with onabotulinumtoxinA doses ≥20 U for GLs. Methods: This 48-week, double-blind study compared 40, 60, and 80 U onabotulinumtoxinA vs 20 U and placebo in women with moderate or severe dynamic GLs on the Allergan Facial Wrinkle Scale. The following parameters were evaluated: the percentage of subjects with investigator-assessed ≥1-grade Facial Wrinkle Scale improvement from baseline at maximum frown (responders) at Week 24; the estimated median duration of response; the proportion of mostly/very satisfied responders on the Facial Line Satisfaction Questionnaire follow-up Items 1 to 5; and treatment-emergent adverse events. Results: The modified intent-to-treat population (N = 226) had a mean age of 48.0 years, with similar baseline GL severity between treatment groups. Week 24 responder rates were 0% for placebo and 16.0%, 32.0%, 30.6%, and 38.5% for onabotulinumtoxinA 20, 40, 60, and 80 U, with significant ( P < 0.05) differences for 40 and 80 U vs 20 U. Median duration of response was longer with all higher doses vs 20 U (≥24.0 vs 19.7 weeks; P < 0.05 vs 20 U at Week 24). Facial Line Satisfaction Questionnaire results indicated high subject satisfaction. The incidence and severity of treatment-emergent adverse events did not exhibit a dose-response effect. Conclusions: GL treatment with onabotulinumtoxinA doses >20 U demonstrated longer duration of response and higher patient-reported satisfaction vs the on-label 20-U dose with no apparent impact on safety variables. Level of Evidence: 2: